Levels of governance in policy innovation cycles in community education: the cases of education for sustainable development and climate change education - Kolleck, N. (2017)
While there is little doubt that social networks are essential for processes of implementing social innovations in community education such as Climate Change Education (CCE) or Education for Sustainable Development (ESD), scholars have neglected to analyze these processes in the multilevel governance system using Social Network Analysis. In this article, we contribute to closing this research gap by exploring the implementation of CCE and ESD in education at the regional and global levels. We compare the way CCE is negotiated and implemented within and through the global conferences of the UN Framework Convention on Climate Change (UNFCCC) with the way the UN Decade of ESD is put into practice through networks in five different German municipalities. We argue that the role of social networks is particularly strong in policy areas like CCE and ESD, which are best characterized as multi-level and multi-actor governance. Based on data derived from standardized surveys and from Twitter we analyze the complex interactions of public and private actors at different levels of governance in the two selected policy areas. We find, amongst others, that the implementation of CCE and ESD in community education depends in part on actors that had not been assumed to be influential at the outset. Furthermore, our analyses suggest the different levels of governance are not well integrated throughout the phases of the policy innovation cycle.